2017
DOI: 10.1186/s12936-017-2002-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax genetic diversity and heterozygosity in blood samples and resulting oocysts at the Thai–Myanmar border

Abstract: BackgroundPolyclonal blood-stage infections of Plasmodium vivax are frequent even in low transmission settings, allowing meiotic recombination between heterologous parasites. Empirical data on meiotic products are however lacking. This study examined microsatellites in oocysts derived by membrane feeding of mosquitoes from blood-stage P. vivax infections at the Thai–Myanmar border.MethodsBlood samples from patients presenting with vivax malaria were fed to Anopheles cracens by membrane feeding and individual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…During this stage, meiosis produces haploid recombinant progeny that are then inoculated back into the human host. The co-transmission of multiple genetically distinct clones to the vector is thus central to the generation and maintenance of diversity via sexual recombination [ 19 , 20 ]. As infections decline both within and among hosts, it is expected that effective population size, genetic diversity and gene flow will decrease, eventually leading to inbred, structured populations [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…During this stage, meiosis produces haploid recombinant progeny that are then inoculated back into the human host. The co-transmission of multiple genetically distinct clones to the vector is thus central to the generation and maintenance of diversity via sexual recombination [ 19 , 20 ]. As infections decline both within and among hosts, it is expected that effective population size, genetic diversity and gene flow will decrease, eventually leading to inbred, structured populations [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To allow for inbreeding under the model, we have included the parameter α ∈ [0, 0.5] as specified in Assumption 1. A recent study found compelling evidence of inbreeding and selfing in oocysts from mosquitoes fed on P. vivax blood samples from the Thailand-Myanmar border in 2013 [77]. As a sensitivity analysis, we reran the computations with α= 0.175 (see github notebook) and compared with results for α= 0.…”
Section: Methodsmentioning
confidence: 99%
“…This technology in combination with analysis software like GeneScan™ provides a powerful tool for analyses of microsatellite markers. Few adequate microsatellite markers have been identified for P. malariae compared to P. falciparum the [21,27,28,29] and P. vivax [20,30,31,32]. The previously identified few P. malariae genotyping markers [13,14] showed promising potential and could identify up to 10 distinct alleles for a single locus.…”
Section: It Has Been Argued That Malaria Elimination Programmes Largementioning
confidence: 99%